ANALISIS IMPLEMENTASI KEBIJAKAN PELATIHAN BERBASIS KOMPETENSI BAGI PEMANDU WISATA EDUKASI DI BANYUWANGI PARK - Kanom; Alfani Nabila; Bella Angelica; Ade Aulyaning Puji Asyafitri; Putri Pratama Madani (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2026)
Banyuwangi Park is one of the artificial tourist destinations that carries the theme of local culture as well as science, history, and environmental education. This research discusses the importance of improving the quality of tour guides to support professional services and educational tourism experiences for tourists with the aim of knowing how far the manager provides competency training in improving the quality of educational tour guides at Banyuwangi Park. The method used is descriptive qualitative with data collection techniques in the form of interview, observation, and documentation. The results showed that the competency-based training provided was able to improve the ability of educational tour guides to provide interesting and informative explanations according to the competency standards set by the Indonesian Ministry of Manpower. This training has a positive impact on visitor comfort and satisfaction while traveling at Banyuwangi Park. Based on the results of the study, competency-based training is very important in improving the professionalism of educational tour guides and supporting the development of education-based tourism in Banyuwangi.